Stereotypes of Aging: Their Effects on the Health of Older Adults. (12th November 2015) - Dionigi, Rylee A.
Abstract : The purpose of this review is to present findings on the effects of stereotypes of aging on health outcomes related to older adults, such as physical and mental functioning (specifically) and overall well-being and perceived quality of life (more broadly). This review shows that both positive and negative stereotypes of aging can have enabling and constraining effects on the actions, performance, decisions, attitudes, and, consequently, holistic health of an older adult. This review further highlights a variety of limitations in stereotype research in aging contexts, including a lack of qualitative studies focusing on older adult perspectives and the fluctuating definition of what constitutes "good health" during older age.